Potentiated Hsp104 variants antagonize diverse proteotoxic misfolding events - Jackrel, Meredith E. (2014)
There are no therapies that reverse the proteotoxic misfolding events that underpin fatal neurodegenerative diseases including amyotrophic lateral sclerosis (ALS) and Parkinson disease (PD). Hsp104, a conserved hexameric AAA+ protein from yeast, solubilizes disordered aggregates and amyloid, but has no metazoan homologue and only limited activity against human neurodegenerative disease proteins. Here, we reprogram Hsp104 to rescue TDP-43, FUS, and α-synuclein proteotoxicity by mutating single residues in helix 1, 2, or 3 of the middle domain or the small domain of nucleotide-binding domain 1. Potentiated Hsp104 variants enhance aggregate dissolution, restore proper protein localization, suppress proteotoxicity, and in a C. elegans PD model attenuate dopaminergic neurodegeneration. Potentiating mutations reconfigure how Hsp 104 subunits collaborate, desensitize Hsp104 to inhibition, obviate any requirement for Hsp70, and enhance ATPase, translocation, and unfoldase activity. Our work establishes that disease-associated aggregates and amyloid are tractable targets and that enhanced disaggregases can restore proteostasis and mitigate neurodegeneration.